Investigating the status of Ecuador’s lost shark, the Sharpfin Houndshark Triakis acutipinna (Revista de Biología Marina y Oceanografía, 2022)
The Sharpfin Houndshark, Triakis acutipinna, was described in 1968 from a specimen captured from Isla de la Plata, Ecuador. Since then, there have been no confirmed records of the species. To investigate the contemporary occurrence of this ‘lost shark’, a multi-pronged approach was undertaken. This included a literature review, development of an educational poster, and conducting a small number of informal fisher interviews in five coastal communities of Manabí province, Ecuador. Half of the fishers interviewed recognized T. acutipinna and reported its capture as recently as 2010-2015. Despite the preliminary nature of the present study, it suggests that the lost shark of Ecuador persists.